A chemosensory gene family encoding candidate gustatory and olfactory receptors in Drosophila. - Scott, K.; Brady, R.; Cravchik, A.; Morozov, P.; Rzhetsky, A.; Zuker, C.; Axel, R. (Cell, 2001)
A novel family of candidate gustatory receptors (GRs) was recently identified in searches of the Drosophila genome. We have performed in situ hybridization and transgene experiments that reveal expression of these genes in both gustatory and olfactory neurons in adult flies and larvae. This gene family is likely to encode both odorant and taste receptors. We have visualized the projections of chemosensory neurons in the larval brain and observe that neurons expressing different GRs project to discrete loci in the antennal lobe and subesophageal ganglion. These data provide insight into the diversity of chemosensory recognition and an initial view of the representation of gustatory information in the fly brain.